Topiramate Adjunctive Therapy for Partial Seizures - J Gordon Millichap (Pediatric Neurology Briefs)
The efficacy and safety of topiramate (TPM) (6 mg/kg/day) in children age 2 to 16 years, as adjunctive therapy for uncontrolled partial-onset seizures (75% complex partial), with or without secondarily generalized seizures, were evaluated in a multicenter, randomized, double-blind, placebo-controlled trial, organized by the Topiramate YP Study Group.